Chat GPT AIS “Interview” 1, December 2022 - Neves, Pedro Soares (Architecture Image Studies, 2023)
What do you know about architecture image studies ? Architecture image studies is a field that focuses on the visual representation of architectural spaces and structures. This can include the study of architectural drawings and plans, photographs of buildings, and computer-generated images of proposed designs. The goal of architecture image studies is to understand how architects and other design professionals use visual media to communicate their ideas and to analyze the impact of these images on the way that people perceive and experience buildings and other built environments. Some specific topics that might be covered in architecture image studies include the history of architectural representation, the aesthetics of architectural imagery, and the use of digital media in architectural design.